An MSC bone‐homing compound, Rab001, increases bone mass and reduces the incidence of osteonecrosis in a glucocorticoid‐induced osteonecrosis mouse model. (15th December 2020) - Jiang, Min; Liu, Lixian; Xiang, Xuexiang; Liang, Runmin; Qin, Xuelian; Zhao, Jinmin; Wei, Qingjun
Abstract: Currently, there are no effective medications to either prevent or slow the progression of atraumatic osteonecrosis (ON). The objective of this study is to determine the effects of bone‐targeted delivery of mesenchymal stem cells on the prevalence of ON in a glucocorticoid (GC)‐induced mouse model. Eight‐week‐old male BALB/c mice were randomized into groups that received placebo (PL), prednisolone (GC), or concurrent treatments with GC + mesenchymal stromal cells (MSCs), Rab001 or GC + Rab001 + MSCs. Human parathyroid hormone (hPTH) was used as a positive control for bone anabolism. Mice were killed after 30 days, and quantitative measurements of bone mass, bone strength, prevalent ON at the distal femoral epiphysis (DFE) were performed. Angiogenesis was accessed by RNA‐Seq, the circulating angiogenic markers, as well as by immunohistochemical staining. We have showed that a novel agent, Rab001 that can noncovalently bind to mesenchymal stem cells (MSC) and direct them to the bone, prevents the incidence of glucocorticoid‐induced osteonecrosis in the mouse. In contrast, PTH, a bone anabolic treatment, preserves bone mass but sustains higher ON incidence than Rab001+/− MSC‐treated mice. The results of these experiments reveal that glucocorticoids increase the prevalence of ON, and agents that prevent loss of bone vascularity appear to prevent the development of ON. This intervention might be useful in patients with early stages of atraumatic ON. Abstract : Rab001 or in combinational treatment of MSC prevented the incidence of ON in an atraumatic mouse model of ON